Penerapan etnomatematika melalui permainan gobak sodor untuk meningkatkan minat belajar peserta didik kelas III SD Negeri Nglipar II Gunungkidul - Astuti, Qorryantika Meinur; Trisniawati, Trisniawat (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2024)
This research aims to increase the learning interest of class III students at SD Negeri Nglipar II Gunungkidul. This research is classroom action research. The research subjects were 15 class III students at SD N Nglipar II Gunungkidul. Data collection techniques use student learning outcomes tests, observations and questionnaires. Data validity testing is carried out by increasing persistence and triangulation (source, technique and time). The results of research on students' learning interest in mathematics subjects using flat figures using ethnomathematics showed changes in students' learning interest during the learning process as evidenced by an increase in learning interest. Students' interest in ethnomathematics learning in cycle I was 70% and increased to 85% in cycle II. The application of ethnomathematics as a means to motivate, stimulate students, can increase interest in learning, and provide new nuances to mathematics learning